Rise in AeU's Online Master of Education Program - Borneo, Post (Borneo Post, 2018)
Ten years ago, getting a Master's degree in Education meant one of two things for the average working professional: either burning the candle a both ends for a couple of years to make time for both classes and work force to focus on going back to university.